2009
DOI: 10.25011/cim.v32i5.6918
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of vitamin E on central nervous system in streptozotocin-induced diabetic rats

Abstract: Objective: To evaluate the histopathological and antioxidant effects of vitamin E (VE) treatment on brain tissue in streptozotocin (STZ)-induced diabetic rats. Methods: Thirty two male Wistar albino rats were used. The study comprised four groups of 8 rats: Group A - untreated group, group B - diabetic group, group C - VE and group D - diabetic plus VE. In the diabetic groups, diabetes was induced by a single intraperitoneal injection of 65 mg/kg STZ. Vitamin E was given 50 mg/kg/day i.p. for three weeks. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(29 reference statements)
3
6
0
Order By: Relevance
“…Secondly, GSE and vitamin E treatment decreased oxidative stress in the hippocampus and plasma of diabetic rats. Consistent to our results, grape seed proanthocyanidin extracts (Xu et al, 2008) and vitamin E (Hong et al, 2004;Tuzcu and Baydas 2006;Kabay et al, 2009) have been shown to ameliorate increased oxidative stress in the brains of diabetic rats. Also, Sato et al (2001) have stated that grape seed proanthocyanidin extracts have in vivo antioxidant activity and can be as important as vitamin E in preventing ischemia/reperfusion induced oxidative damage and apoptosis in cardiomyocytes by reducing the lipid oxidation and/or inhibit the production of free radicals.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…Secondly, GSE and vitamin E treatment decreased oxidative stress in the hippocampus and plasma of diabetic rats. Consistent to our results, grape seed proanthocyanidin extracts (Xu et al, 2008) and vitamin E (Hong et al, 2004;Tuzcu and Baydas 2006;Kabay et al, 2009) have been shown to ameliorate increased oxidative stress in the brains of diabetic rats. Also, Sato et al (2001) have stated that grape seed proanthocyanidin extracts have in vivo antioxidant activity and can be as important as vitamin E in preventing ischemia/reperfusion induced oxidative damage and apoptosis in cardiomyocytes by reducing the lipid oxidation and/or inhibit the production of free radicals.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…These alterations in the untreated diabetic group had more damage than the ellagic acid-treated diabetic group. Also, in a previous study, it was reported that STZinduced diabetes caused neuronal necrosis areas, hemorrhagic focuses, damaged blood vessels and degenerative changes in cells in diabetic group [34].…”
Section: Discussionmentioning
confidence: 97%
“…This trace element is known to antagonize the toxicity of silver ions (14). Vitamin E is a lipid-soluble chain-breaking antioxidant which protects, especially, biological membranes from lipid peroxidation (15). Deficiency of dietary vitamin E and selenium has been showed to induce a number of lesions in rats depending upon the degree of depletion (16).…”
Section: Introductionmentioning
confidence: 99%